PERSEPSI NEGATIF TENTANG DIET PADA REMAJA PUTRI: STUDI CROSS-SECTIONAL DI KABUPATEN TABANAN - Ni Kadek Muliarsi; Ni Ketut Sutiari (PERSATUAN AHLI GIZI INDONESIA, 2022)
Indonesia bears the three burdens of adolescent malnutrition: malnutrition, obesity, and micronutrient deficiency. Until now, teenage girls understand diet as a lifestyle to reduce food intake and limit the selection of food such as food ingredients and take supplements to lose weight. The purpose of this study was to determine the perceptions of diet among adolescent girls in the Tabanan District. The design of this study is a descriptive study using a cross-sectional approach. This research was conducted in the area of a public health center in Tabanan District, from March until May 2022. The technique of selecting the study set uses a purposive sampling technique. The sample of this study was teenage girls aged around 15 to 19 years who were in the public health center I, II, and III areas of Tabanan. The sample of this study was 106 people, which was obtained using a simple sampling technique, and the research analysis used univariate analysis. This study shows that the average age of female adolescents who became the research sample was 17 years, and most were senior high school students (73.58%). (55.8%) teenagers have a negative perception of diet than (46.2%) of others who have a positive perception. Therefore, it is recommended for teenagers to be wiser in sorting the information received to minimize negative perceptions about diet.